The possible protective role of green tea extract on the intestinal mucosal changes induced by fluoride on adult albino rats - M. Abo El Wafa, Ssahar; Abdel-Mohsen Abdel-Aziz, Eman; M. Shawky, Lamiaa; S. Zaki, Mariam (International Journal of Pharmacology and Toxicology, 2020)
Background: Fluoride is an inorganic element present everywhere in the environment and has cumulative toxic effects from prolonged ingestion. Green tea used since ancient times as a medical drink due to its multiple health benefits owing to its anti-oxidative and anti-apoptotic activities. Aim: To the best of our knowledge there were no studies until now concerning the possible protective role of green tea extract on the intestinal mucosal changes induced by fluoride on adult albino rats, so this work tried to investigate this role. Materials and Methods: Forty male adult albino rats randomly and equally divided into four groups, Group I: received distilled water only orally via a gastric tube. Group II: received green tea extract (GTE) 150 mg/kg dissolved in distilled water and freshly prepared for 35 days. Group III: received sodium fluoride (NaF) once daily oral dose of 10 mg/kg dissolved in distilled water for 35 days. Group IV: received NaF in the same dose as group III concomitant with GTE as the previously adjusted dose for 35 days. Body weight of all the studied groups was recorded at the start and after 35 days from the beginning of this study. After that the study tested the antioxidant and oxidant parameters in intestinal tissue as MDA, reduced GSH, and CAT, histopathological and immunohistochemical examination of intestinal tissue using PCNA marker were also included. Results: the rate of weight gain was little in NaF group compared to other groups. Concomitant administration of GTE with NaF resulted in highly significant decrease in MDA level, highly significant increase in reduced GSH level and highly significant elevation in CAT level when compared with NaF group. Many of abnormalities as moderate increase in goblet cell mass and highly expression of PCNA stain in a form of brown nuclear coloration were detected in intestinal tissues in NaF group by histopathological and immunohistochemical study that improved with administration of GTE. Conclusion: concomitant administration of GTE was improved the biochemical, histopathological and immunohistochemical alterations in intestinal mucosa that treated with NaF.Â Â Â